Basal metabolic rate correlates with excess postexercise oxygen consumption across different intensities - Shu-Chun Huang; Kuan-Hung Chen; Watson Hua-Sheng Tseng; Lan-Yan Yang; Ching-Chung Hsiao; Yi-Chung Fang; Chen-Hung Lee (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Both the basal metabolic rate (BMR) and excess postexercise oxygen consumption (EPOC) can be influenced by physical training and are associated with body composition and aerobic capacity. Although a correlation between the two is expected, this relationship has not been explored. Our hypothesis is that a higher BMR is correlated with lower EPOC. Methods Fifty-four healthy participants with a mean age of 33 years were enrolled and instructed to visit the exercise laboratory five times within a 3-week period. These visits included one for the BMR measurement, one for the incremental exercise test (INC), and three for the constant work rate (CWR) test at low (35% of the maximal work rate, 15 min), moderate (60%, 10 min), and high intensities (90%, 4 min). The CWR tests were conducted at low, moderate, and high intensities in random order. After each CWR test, the EPOC and the ratio of EPOC to oxygen consumption during exercise (OC) were calculated. Venous blood samples were collected immediately to assess the blood lactate concentration (BLa). Results The EPOC, EPOC/OC, and BLa increased with increasing intensity of the CWR tests. BMR exhibited an inverse correlation with EPOC/OC across the three CWR settings with correlation coefficients -0.449 in low (p = 0.003), -0.590 in moderate (p = 0.002), and -0.558 in high intensity (p < 0.001). In the stepwise regression analysis, the BMR emerged as the most significant predictor of EPOC/OC compared to the BLa, age, BMI, and various parameters derived from the INC and CWR CPET. Additionally, coupling EPOC/OC with CWR exercises of identical duration and relative intensity provides a viable method for interindividual comparisons. Conclusions The BMR is a major predictor of EPOC/OC and demonstrates a negative linear correlation across various CWR intensities. This study improves the understanding of the physiological link between BMR and EPOC and introduces an applicable approach for utilizing EPOC in future research.